Diverse Rice Landraces of North-East India Enables the Identification of Novel Genetic Resources for Magnaporthe Resistance - Umakanth, Bangale; Vishalakshi, Balija; Sathish Kumar, P.; Rama Devi, S. J. S.; Bhadana, Vijay Pal; Senguttuvel, P.; Kumar, Sudhir; Sharma, Susheel Kumar; Sharma, Pawan Kumar; Prasad, M. S.; Madhav, Maganti S. (Frontiers in Plant Science, 2017)
North-East (NE) India, the probable origin of rice has diverse genetic resources. Many rice landraces of NE India were not yet characterized for blast resistance. A set of 232 landraces of NE India, were screened for field resistance at two different hotspots of rice blast viz., IIRR-UBN, Hyderabad and ICAR-NEH, Manipur in two consecutive seasons. The phenotypic evaluation as well as gene profiling for twelve major blast resistance genes (Pitp, Pi33, Pi54, Pib, Pi20, Pi38, Pita2, Pi1, Piz, Pi9, Pizt and Pi40) with linked as well as gene-specific markers, identified 84 resistant landraces possessing different gene(s) either in singly or in combinations and also identified seven resistant landraces which do not have the tested genes, indicating the valuable genetic resources for blast resistance. To understand the molecular diversity existing in the population, distance and model based analysis were performed using 120 SSR markers. Results of both analyses are highly correlated by forming two distinct subgroups and the existence of high diversity (24.9% among the subgroups; 75.1% among individuals of each subgroup) was observed. To practically utilize the diversity in the breeding programme, a robust core set having an efficiency index of 0.82 which consists of 33 landraces were identified through data of molecular, blast phenotyping and important Agro-morphological traits. The association of eight novel SSR markers was revealed through genome-wide association analysis. This also consists of important agronomic traits including leaf and neck blast resistance. The current study focuses on identifying novel resources having field resistance to blast as well as markers which can be explored in rice improvement programmes. It also entails the development of a core set which can aid in representing the entire diversity for efficiently harnessing its properties to broaden the gene pool of rice.